The Role of Territorial Promotion Agencies in the Creation of a Valuable Tourist Experience. An Italian Case History - Di Vittorio, Arianna (European Scientific Journal, ESJ, 2018)
With the passage of time, the offer made by tourism companies has undergone important changes, becoming more and more configured as a unique and memorable consumer experience, able to activate the sensory system of the consumer and to stir up emotions. The experiential marketing27 uses the experiences lived by consumer as marketing tool so as to make the consumer perceive a higher added value, thanks to the involvement of the senses and emotions. Also within the tourism sector, the need to cope with the new needs of tourists led the companies on the road to experiential differentiation. In today’s society, consumption is no longer a private and personal act, but a real “social event” in the sense that a product is purchased not so much for its functional value, as for the meaning it assumes for those who use it or consume it and for its own social relationships. The consumer experience therefore generates a noticeable involvement for consumer and for its own social relations: the individual seeks, for this reason, products and services with a symbolic value, that allow him to fully manifest his personality. “To consume means to satisfy one’s own needs, but also to create and maintain social relationships” (Douglas & Isherwood, 1989). The paper focuses on the role of Tourist Promotion Agencies, particularly on the Agency “Tourism Imperial Apulian”, reference subject for marketing, reception and promotion of Local Tourist System “Puglia Imperiale”, and new reference for creation of a quality tourist experience. The methodology used in the paper is a descriptive empirical analysis; after a view on the variables important to create a valuable experience for tourists and a statistical reflection on the data related to the incoming in Puglia from 2007 to 2014, the Author describes the strategies adopted in the case history. This empirical analysis aims to confirm the promotional validity of the "Puglia Imperiale" Tourist Agency and, above all, to witness the creation of a new territorial identity brand evolved into a real tourism product, through the activity of a Management Agency of the destination.